Farmers Respons to Garlic Development On Upland Program in East Lombok Regency - Idiatul Fitri Danasari; Ni Made Wirastika Sari; Rifani Nur Sindy Setiawan (Jurnal Biologi Tropis, 2022)
East Lombok Regency is one of locations that designated as the location for garlic development in Indonesia. The potential for garlic development is supported by the availability of land scattered in a number of sub-districts in East Lombok Regency such as Sembalun District, Suela District, Wanasaba District, and several other buffer districts. Seeing this potential, through The Development of Integrated Farming System in Upland Areas (Upland)’s Program, the Government of East Lombok Regency focuses on developing garlic. The purpose of this study was to determine the characteristics and responses of garlic farmers to the Upland Program in East Lombok Regency. The research was conducted by quantitative descriptive method with survey and interview. The selection of respondents used a purposive sampling technique on farmers who received and implemented the Upland Program in 2021-2022. Method of data analysis using multiple linear regression test. The results showed that the response of farmers was very high in garlic development activities in the Upland Program in East Lombok Regency. There are several variables that have a positive and significant effect on farmer responses, namely income (X3), land area (X4), and farming experience (X5). Meanwhile, age and education variables have no significant effect on farmers' responses.